Hemolytic Disease of the Fetus and Newborn in an Integrated Health Care System - Fassett, Michael J.; Khadka, Nehaa; Xie, Fagen; Shi, Jiaxiao; Chiu, Vicki Y.; Im, Theresa M.; Kim, Sunhea; Mensah, Nana A.; Park, Daniella; Mao, Carol; Molaei, Matthew; Lin, Iris; Getahun, Darios (American Journal of Perinatology, 2025)
Hemolytic disease of the fetus and newborn (HDFN) is associated with significant infant morbidity and mortality. Characteristics of pregnancies impacted by HDFN are not well understood. Therefore, this study examines maternal and infant characteristics based on HDFN status in a large, integrated health care system in the United States.This was a population-based, retrospective cohort study of 464,711 pregnancies that received care at Kaiser Permanente Southern California (KPSC) hospitals from January 2008 to June 2022. HDFN cases were ascertained using a validated algorithm of structured and unstructured data elements. HDFN due to ABO alloimmunization alone was excluded. Adjusted odds ratios (aORs) derived from logistic regression were used to describe the association between maternal and infant characteristics and HDFN diagnosis as well as adverse perinatal outcomes. For rare events, Firth's bias-reduced logistic regression was applied.A total of 136 HDFN pregnancies with 138 HDFN births (live births = 137; stillbirth = 1) were observed in the study. Of three twin pregnancies, all but one fetus had an HDFN diagnosis. HDFN diagnosis was associated with a maternal age of ≥35 years (aOR: 1.74; 95% confidence interval [CI]: 1.13–2.67), hypertension (2.07; 0.96–4.50), renal disease (3.43; 1.75–6.70), and multiparity (4.95; 2.73–8.95). Furthermore, HDFN diagnosis was associated with birth at 33 to 34 weeks (aOR: 5.72; 95% CI: 2.78–11.78) and 35 to 36 weeks (3.76; 2.38–5.94), and neonatal jaundice (3.11; 2.20–4.41). Birth weight ≥4,000 g was associated with lower HDFN diagnosis odds than normal weight (2,500–3,999 g; aOR: 0.36; 95% CI: 0.14–0.90). Hispanic race/ethnicity was associated with a lower HDFN diagnosis risk than non-Hispanic White (aOR: 0.63; 95% CI: 0.43–0.93).This study identified clinical and demographic factors linked with HDFN diagnosis, including specific maternal characteristics, medical/obstetrical factors, and neonatal factors, within a large, integrated health care system that can help inform management plans.
Keywords: adverse perinatal outcomes; chronic maternal hypertension; HDFN; hemolytic disease; neonatal jaundice; obstetrical care; preterm birth